Research of the stages of the distribution of international cargo traffic processing in combined transportation - Альошинський, Євген Семенович; Світлична, Софія Олександрівна; Виборнова, Юлія Юріївна (Technology audit and production reserves, 2013)
This article highlights the key issues concerning the improvement the efficiency of the operation of merchant seaports and stations, due to the study and improvement of the international cargo traffic organization system. On the basis of the analysis of the current state of the port transportation hubs development the article presents the gradual process of the import and transit goods processing, with the definition of tasks on its operation improvement and their possible solutions. The method of dynamic programming was developed to create the most advantageous technological scheme of on arrival-operations execution and simulation method of dynamic coordination consistent cargo traffic supply. As a result of the research a number of improvements were suggested at each stage of processing of import and transit cargoes in combined transportation, which can be used in the formation of rational modes of international goods transportation.